Gender approach to the education of primary school students - Umirzakovich, Temirov Kuanysh; Saibulatovna, Zhubakova Saule; Nizatil, Temirkulova; Dmitrievna, Li Yelena (International Journal of Innovative Research and Scientific Studies, 2025)
Under the conditions of the liberalization of sexual morality, social and cultural stereotypes of female and male behavior are changing, and gender roles are becoming mixed, which in turn leads to changes in children’s behavior. These trends contribute to various personality deformations, emotional instability, and a lack of behavioral guidelines for children. This makes the research on gender education for primary school students relevant. The development and testing of an original variant of the content of gender education in primary school were conducted based on mixed methods: surveys, observations, conversations, S. Bem’s Sex and Gender Questionnaire, the Methodology of Gender and Age Identification (L.N. Belopolskaya), and the methodology ‘Draw Yourself’ (A.M. Prikhozhan and Z. Vasiliauskaite). Research Results: Based on the conducted analysis, an original variant of the content of gender education was developed. The criteria, indicators, and levels of gender maturity of primary school students were determined. A differentiated approach to the upbringing of boys and girls is necessary, taking into account gender characteristics. The proposed innovative approach, including forms and methods of education such as training sessions, case analysis, and role-playing games, enhances the effectiveness of the gender education program for students.